Why prevention of repeat abortion is so challenging: psychosocial characteristics of women at risk. (2nd January 2017) - Leeners, Brigitte; Bieli, Simone; Huang, Dorothy; Tschudin, Sibil
Abstract: Objectives: Abortion rates have declined in recent decades; however, the rate of repeat abortion remains high. In order to identify keys to making efficient interventions against repeat abortion, our objectives were: to assess the percentage of repeat abortions in women opting for termination of pregnancy over a period of 1 year; to identify the risk factors for repeat abortion; and to assess the characteristics of women who opted for a further pregnancy termination despite having received standard post-abortion care. Methods: A retrospective cross-sectional survey was carried out among 362 women who underwent pregnancy termination during a 1-year period. Women with and without repeat abortion were compared with regard to age, nationality, marital status, parity and use of contraception. In a subsample of 160 women who were available for follow-up over 4 years, those who underwent a further pregnancy termination during the observation period were also analysed qualitatively. Results: The rate of repeat abortion was 30.1% in the survey population. Age and immigrant status were identified as risk factors. The use of long-acting reversible contraception (LARC) was significantly higher after repeat abortion than after a first termination of pregnancy. Among women with repeat abortion in the follow-up group, those with psychological problems tended to discontinue contraception and those with partnership conflicts were prone to using unreliable contraceptive methods. Conclusion: Aside from promoting LARC methods, strategies to reduce repeat abortion should consider the psychosocial risk factors and characteristics of women at risk identified in this study. An interdisciplinary approach including social care and counselling would be the most appropriate means to enable this.